The archaeology of indigenous herders in the Western Cape of southern Africa - Arthur, C. (Southern African Humanities, 2021)
Archaeologists commonly cite the high mobility of pastoralists and destruction by modern development and agriculture to explain the low number of herder sites known to date. This paper presents an alternative explanation. Here it is argued that the type of research itself is at least partly responsible for the limited results. The focus on deeply stratified archaeological deposits in caves and coastal middens at the expense of open landscape surveys, the persistence of typological classification and the lack of research into the eighteenth- and nineteenth-century Khoekhoen are presented as causal factors. A dominant theoretical model links all three. The cultural identity or 'dichotomy model' requires deep deposits and large numbers of artefacts in order to classify assemblages as either produced by hunters or by herders. The dominant model also encourages a focus on the pre-colonial period, as hunter and herder identities are thought to have become less distinct after colonial settlement.